Model Analisis Risiko Bencana Transportasi Bahan Beracun dan Berbahaya Industri di Kabupaten Serang, Provinsi Banten - Prihartanto, Prihartanto; Raharjo, Akhmadi Puguh; Zahro, Qoriatu (Jurnal Teknologi Lingkungan, 2019)
ABSTRACTPulo Ampel Industrial Zone in Serang Regency is an industrial zone with a high level of threat from a technological hazard. One possible route this threat can be manifested is in the form of explosion potential from the storage and transport tanks of toxic and dangerous materials e.g. Ethylene and Butadiene gases. Within the framework of disaster risk reduction, disaster risk analysis is carried out which includes the analysis of threats and vulnerabilities along the path of transport of these hazardous materials. To determine the level of explosion hazard, due to the occurrence of transportation accidents, modeling using ALOHA® (Areal Locations of Hazardous Atmospheres) software, which was developed by the United States Environmental Protection Agency (US EPA), was carried out. The model used in this study was the BLEVEs (Boiling Liquid Expanding Vapor Explosions) scenario during gas transportation using ISO Tank, which represents the worse possible scenario. Meanwhile, disaster vulnerability analysis is calculated based on social vulnerability aspect which includes population density and vulnerable group parameters by utilizing the scoring method in accordance to Head of BNPB Decree No.2 of 2012. Based on the hazard and vulnerability level, disaster risk maps are obtained along the Ethylene and Butadiene transport lines covering the information related to the area of the explosion which intersected with population settlement in Serang Regency, Banten Province.Keywords: risk reduction, trasportation, hazardous materials, vulnerabilities, explotionABSTRAKZona Industri Pulo Ampel di Kabupaten Serang merupakan zona industri dengan ancaman bencana kegagalan teknologi yang relatif tinggi. Ancaman bahaya yang dapat ditimbulkan diantaranya berupa potensi ledakan dari tangki-tangki penyimpanan maupun tangki transportasi bahan berbahaya dan beracun (B3) terutama gas Etilena maupun Butadiena. Dalam rangka pengurangan risiko bencana, maka dilakukanlah analisis risiko bencana terhadap tangki transportasi B3 yang meliputi analisis ancaman dan kerentanan di sepanjang jalur transportasi B3 tersebut. Untuk menentukan salah satu tingkat bahaya yang berupa ledakan akibat kecelakaan transportasi gas dilakukanlah pemodelan dengan menggunakan perangkat lunak modeling ALOHA® (Areal Locations Of Hazardous Atmospheres) yang dikembangkan oleh United States Environmental Protection Agency (US EPA). Model yang digunakan di dalam kajian ini menggunakan skenario ledakan terburuk berupa skenario BLEVEs (Boiling Liquid Expanding Vapor Explosions) pada saat transportasi gas menggunakan ISO Tank. Sementara analisis kerentanan bencana dihitung berdasarkan aspek kerentanan sosial yang meliputi parameter kepadatan penduduk dan kelompok rentan dengan menggunakan metode skoring sesuai Perka BNPB No. 2 Tahun 2012. Berdasarkan tingkat bahaya dan kerentanan tersebut diperolehlah peta risiko bencana di sepanjang jalur transportasi gas Etilena dan Butadiena yang meliputi informasi terkait luas area permukiman penduduk terdampak ledakan di Kabupaten Serang, Provinsi Banten.Kata kunci: pengurangan risiko, transportasi, bahan beracun dan berbahaya, kerentanan, ledakan